Cultural Memory and Intellectual History: Locating Austrian Literature - David S. Luft (Studies in 20th & 21st Century Literature, 2007)
"Cultural Memory and Intellectual History: Locating Austrian Literature" is an essay about the way intellectuals contributed to reshaping cultural memory in Austria after the Second World War. By cultural memory I mean collective memory of the cultural past, of the creative achievements of a society, in this case the achievements of writers. At the center of my story are five intellectuals trying to make sense of the significance of Austrian literature and the Austrian cultural past, usually in a mode of advocacy, both recalling and creating a cultural past for the tiny postwar republic. Cultural memory of this kind is both collective, in the sense of repeating what is known and accepted, and individual, in the sense of being actively selective and inventive. I am concerned here primarily with five cultural commentators who helped to shape understandings of Austrian literature in the early years of the Second Republic: Heimito von Doderer (1896-1966), Friedrich Heer (1916-1983), Ivar Ivask (1927-1992), Herbert Eisenreich (1925-1986), and Herbert Seidler (1905- ). These intellectuals developed a view of Austrian literature that contributed to discourse about Austrian national identity by both expressing and refining Austrian understandings of their cultural past. In my discussion of their work, I concentrate on five texts that defined the concept of Austrian literature between 1955 and 1970.
Keywords: Cultural Memory; Austrian Literature; Austria; World War II; Second World War; collective memory; cultural past; Austrian cultural past; postwar; Heimito von Doderer; Friedrich Heer; Ivar Ivask; Herbert Eisenreich; Herbert Seidler; national identity